The Impact of Teacher Interaction and Knowledge Mastery on Students’ English Class Satisfaction - Delita Rosliana; Dhevina Tiara Dharmansyah (MIREJ: Multidisciplinary Innovation Research Journal, 2025)
This study examines the effect of teacher-student interaction and teacher knowledge mastery on student satisfaction in English language learning classes. The quantitative method uses a purposive sampling technique, with the number of data collected as many as 291 respondents aged 16 to 26 years consisting of high school and university students through a structured questionnaire distributed via Google Forms. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that only measurement constructs related to evaluation and assessment significantly affect student satisfaction. In contrast, teacher qualifications and interactions do not show statistically significant direct or indirect effects. These results indicate that the level of student satisfaction is mainly shaped by how effectively teachers carry out assessments, highlighting the importance of clear, objective, and transparent evaluation methods in English language teaching.